An adhesion–ploughing friction model of the interface between concrete and silty clay. (2nd May 2023) - Pan, Jingjing; Wang, Boxin; Wang, Qing; Ling, Xianzhang; Fang, Ruichang; Liu, Jiaqi; Wang, Zihao
Highlights: An adhesion–ploughing friction model of the interface was established. The surface morphological characteristics of concrete was considered in the model. The shear strength at the interface was explained by the modern friction theory. Abstract: The shear behavior of the interface between concrete and soil is of great significance for the safety and stability of various building structures. The purpose of this study is to investigate the shear characteristics of concrete–silty clay interface under concrete surface roughness, normal stress and moisture content by modern friction theory. An adhesion–ploughing friction model was established to predict the shear strength of concrete–silty clay interface based on the friction properties of concrete and silty clay. The influence of concrete surface roughness, normal stress and moisture content on the interfacial shear behavior was considered in the model. The model was verified by a series of direct shear tests. The shear load rate of the direct shear test was 0.8 mm/min. The roughness of concrete was achieved by Fila 3D printing technology. The relationship between the shear strength of the interface and the surface roughness of the concrete, normal stress and moisture content was explained by the modern friction theory. The results showed that the shear strength of concrete–silty clay interface was positively correlated with normal stress and concrete surface roughness, and negatively correlated with moisture content. The shear strength of concrete–silty clay interface was composed of adhesion force and ploughing force. The surface roughness of concrete improved the shear strength by affecting the ploughing force of the interface. The adhesion force was related to normal stress and moisture content. The adhesion–ploughing friction model can effectively predict the shear strength of concrete–silty clay interface.